La ley de Okun en el Perú: 1970-2000 - Garavito, Cecilia (Pontificia Universidad Católica del Perú. Fondo Editorial, 2003)
The objective of this work is to analyze the existing relation between employment, unemployment and production, by means of the estimation of the Okun coefficient for the Peruvian Economy. A previous step consists in the estimation of the employment-production elasticity. Both parameters are important elements for macroeconomic policy design, and the evaluation of its effects on employment and welfare. Based on a cointegration analysis we find a positive long-term relation between the employment rate and Lima's GDP throughout the period, where the employment rate rises in 0.0288 percentage points for a rise of 1000 nuevos soles of 1979. We also estimate an Okun coefficient of 0.0845, its low value is only comparable with those of Japan, Bolivia and Argentina. In Peru's case, the reason for this low coefficient can be found in the procyclical behavior of the labor force, and in the fact that workers retire from the labor market when they lose their post. We also find that the rate of growth of the GDP must be at least of 3.31% in order to keep the unemployment rate from rising, and of about 11% to lowerthe unemployment rate in one point. Finally, we estimate recursive Okun coefficients based on the cyclical components of the series, which gives us a range between 0.02 and 0.12 for the whole period.

El objetivo de este artículo es explorar la relación entre el empleo, el desempleo y el producto, para lo cual estimamos el coeficiente de Okun. Un paso previo es el cálculo de la elasticidad empleo-producto. Ambos parámetros son importantes para el diseño de políticas macroeconómicas y la evaluación de sus efectos sobre el empleo y el bienestar. A partir de un análisis de cointegración encontramos que existe una relación positiva de largo plazo entre la tasa de empleo y el PIB de Lima Metropolitana a lo largo del periodo estudiado, donde por cada 1000 nuevos soles de 1979 de elevación del producto, la tasa de empleo se elevará en 0.0288 puntos porcentuales. Estimamos también un coeficiente de Okun de 0.0845, nivel bastante bajo, y solamente comparable a los coeficientes de Japón, Bolivia y Argentina. En el caso del Perú la baja sensibilidad de la tasa de desempleo a los cambios en el producto se debe al comportamiento procíclico de la fuerza laboral, y al hecho de que al perder su empleo los trabajadores se retiran del mercado. Asimismo, encontramos que la tasa de crecimiento del producto debe ser de al menos 3.31% para que el desempleo no se eleve, debiendo ser de alrededor de un 11% para reducir la tasa de desempleo en un punto porcentual. Finalmente, estimaciones de coeficientes recursivos de Okun a partir de los componentes cíclicos de las series nos dan un rango de entre 0.02 y 0.12 para el periodo en estudio.
Keywords: Economía; Economy; Economic Rationality; Homo Economicus; Utility; Neoclassical Economics; Evolutionary Economics; Behavioural Economics; Institutional Economics; https://purl.org/pe-repo/ocde/ford#5.02.01